Acute Flaccid Paralysis by Enterovirus D68 Infection: First Italian Description in Adult Patient and Role of Electrophysiology - Ceccanti, Marco; Sbardella, Emilia; Letteri, Federica; De Michele, Manuela; Falcou, Anne; Romanzi, Federica; Onesti, Emanuela; Inghilleri, Maurizio (Frontiers in Neurology, 2017)
A Peruvian woman was admitted to the Emergency Department, due to an acute flaccid paralysis of the upper limbs that progressively involved also lower limbs and respiratory muscles. She previously suffered from non-Hodgkin’s lymphoma and had to undergo hematopoietic stem cell transplantation. A MRI showed a T2 hyperintensity in the anterior and central region of the cervical segment with an elective involvement of grey matter. This finding, combined with other clinical, laboratory and electrophysiological data, led to a diagnosis of acute flaccid paralysis. Enterovirus D68 was isolated in the patient’s cerebrospinal fluid (CSF), plasma and throat swab. To our knowledge, this is the first Italian case of acute flaccid paralysis by Enterovirus D68 infection in an adult. The diagnostic assessment and management of acute flaccid paralysis by Enterovirus D68 are discussed.